(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
The literary avant-garde represents a cosmopolitan trend in Latin America, but in many writers there is also an important concern about national identity. This article shows how Juan Emar, a cosmopolitan Chilean author, takes part in the discussion about national art during the 1920’s and 1930’s. If artistic activity carries a national identity, he proposes, in his Notas de Arte, it appears in representation as a process, not as an object. The novel Miltín 1934 (1935) will put into practice this rule by showing the lapse of 19th century national pact and the author’s reluctance to commit to a new nationality, collective and popular, that will be constructed throughout the 20th century.